Polish Surnames Ending in -ski in the Anthroponymicon of Lutsk (Linguostylistic Studies, 2020)
For researchers of recent decades, it is important to study the anthroponymic systems of the people who have been living with ethnic Ukrainians for a long time. From the point of view of Ethnosociology, Lutsk has been the place of residence for the representatives of various ethnic groups and nationalities, including Jews, Poles, Russians, Germans, Czechs, and others. The surnames of people who live in Lutsk are the main means of official identification of the family in the society and they directly reflect the realities of the society of the time in which they originated and function.The article analyzes the Polish surnames in -ski / -cki of people who lived in Lutsk. They were selected from the metric books of the State Archives of Volyn region and act records of the birth of Lutsk City Council. To identify anthroponymic material with its specific features characteristic of Polish anthroponymy, the methods of inventory and systematization, as well as the method of etymological analysis were used. Using the method of semantic analysis, the linguistic qualification of surnames according to their creative basis was carried out.The ethnic varieties of the anthroponymic material prompts the identification of Polish and Polonized surnames involved in the analysis,  created on the basis of the East Slavic lexemes with the Polish elements. Therefore, the emphasis is laid on the identification of  the Polish vocabulary and, in particular, its specific phonetic and word-forming elements.It was found that the analyzed model is rich in oykonym surnames. Their creative bases were actually Polish geographical names (Gawroński, Gałęzowski, Sikorski) and the so-called “Kresy” (Biliński, Hoszowski, Lityńskі) and “mixed” names of settlements (Baczyński, Jaroszyński, Żmudziński). Anthroponyms originated from nouns (Marcinowski, Stasowski, Waclawski) and appellation bases (Kolankowski, Łabudziński, Owsiński) are also distinguished among the surnames.
Keywords: anthroponym,; surname,; Polish anthroponymy,; oikonym,; appellative,; personal name,; suffix.